Spectroscopic and Electronic Properties of Molybdacarborane Complexes with Non‐innocently Acting Ligands. Issue 36 (30th May 2019) - Schwarze, Benedikt; Sobottka, Sebastian; Schiewe, Robert; Sarkar, Biprajit; Hey‐Hawkins, Evamarie
Abstract: The molybdacarboranes [3‐{L‐κ 2 N, N}‐3‐(CO)2 ‐ closo ‐3, 1, 2‐MoC2 B9 H11 ] (L=2, 2′‐bipyridine (2, 2′‐bpy, 1 a ) or 1, 10‐phenanthroline (1, 10‐phen, 1 b )) incorporating well‐known potentially non‐innocent ligands (CO, 2, 2′‐bpy, 1, 10‐phen) and the "non‐spectator" nido ‐carborane ([η 5 ‐C2 B9 H11 ] 2− ) ligand were prepared and fully characterised. High‐resolution mass spectrometry, single‐crystal X‐ray diffraction methods, spectroscopy (IR, (resonance) Raman, NMR), cyclic voltammetry and spectroelectrochemistry (electrochemical properties) were supported by theoretical investigations of the electronic structure (DFT, CAS‐SCF, TD‐DFT). Abstract : The molybdacarboranes [3‐{L‐κ 2 N, N}‐3‐(CO)2 ‐ closo ‐3, 1, 2‐MoC2 B9 H11 ] (L=2, 2′‐bipyridine (2, 2′‐bpy, 1 a ) or 1, 10‐phenanthroline (1, 10‐phen, 1 b )) incorporating well‐known potentially non‐innocent ligands (CO, 2, 2′‐bpy, 1, 10‐phen) and the "non‐spectator" nido ‐carborane ([η 5 ‐C2 B9 H11 ] 2− ) ligand were prepared and fully characterised. High‐resolution mass spectrometry, single‐crystal X‐ray diffraction methods, spectroscopy (IR, (resonance) Raman, NMR), cyclic voltammetry and spectroelectrochemistry (electrochemical properties) were supported by theoretical investigations of the electronic structure (DFT, CAS‐SCF, TD‐DFT).